2010
DOI: 10.1590/s1984-82502010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the melting temperature, heat of fusion, and purity analysis of different samples of zidovudine (AZT) using DSC

Abstract: The determination of chemical purity, melting range, and variation of enthalpy in the process of characterizing medicines is one of the principal requirements evaluated in quality control of the pharmaceutical industry. In this study, the method of purity determination using DSC was outlined, as well as the application of this technique for the evaluation of commercial samples of zidovudine (AZT) (raw material) supplied by different laboratories. To this end, samples from six different laboratories (A, B, C, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 15 publications
2
32
0
3
Order By: Relevance
“…Araújo et al have used DSC for determining the purity of substances with a fast and reliable technique for eutectic systems, in which melting is not accompanied by thermal decomposition of the material. Those authors found that the main advantages of the DSC, over chromatography and spectroscopy, are that the analysis of all the impurities normally does not require standards except, for the main compound, and permits simultaneous measurements of the melting range and variation of enthalpy [35]. The sample WE010 showed a purity of 98.87 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Araújo et al have used DSC for determining the purity of substances with a fast and reliable technique for eutectic systems, in which melting is not accompanied by thermal decomposition of the material. Those authors found that the main advantages of the DSC, over chromatography and spectroscopy, are that the analysis of all the impurities normally does not require standards except, for the main compound, and permits simultaneous measurements of the melting range and variation of enthalpy [35]. The sample WE010 showed a purity of 98.87 %.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have used the thermal and nonthermal techniques in the physicochemical characterization of herbal products [35], as well as of other synthetic substances with biological activity potential [28][29][30][31][32]. All those studies showed the relevance of the thermal analysis in the determinations of the thermal parameters and stabilities of those products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are definitive advantages to employing multiple thermal analysis methods to attain varying views of the physicochemical properties of pharmaceuticals. The determination of the key physical and chemical properties of a new material is essential [16][17][18][19][20][21][22][23].…”
Section: Azelastine-hcl Is 4-(4-chlorobenzyl)-2-[(4rs)-1-methylhexahmentioning
confidence: 99%
“…The melting transitions of a pure 100% crystalline material should be infinitely sharp, but impurities or defects in the crystal structure will broaden the melting range and lower the final melting point to a temperature lower than T o [23]. Purity determination is officially listed in Merk index [25].…”
Section: Application Of Differential Scanning Calorimetry For Purity mentioning
confidence: 99%